W. Africa : : Visits to West Africa, Major Vischer - Vischer, Hanns; Great Britain Colonial Office; National Archives (Great Britain); Adam Matthew Digital (Adam Matthew Digital, 1935)
Colonial Office file concerning plans for a visit by Hanns Vischer to various locations in British West Africa, to inspect and report on schools and other educational institutions